Determination of Skeletal Tumor Burden on (18)F-Fluoride PET/CT - Rohren, Eric M. (J Nucl Med, 2015)
The purpose of this study was to define a method to assess skeletal tumor burden with (18)F-labeled sodium fluoride PET/CT ((18)F-fluoride PET/CT) and evaluate the reproducibility of these measurements. METHODS: Ninety-eight consecutive patients (90 men; mean age ± SD, 65.7 ± 14.2 y) underwent 158 (18)F-fluoride PET/CT scans for evaluation of skeletal metastatic disease. In order to determine the mean normal bone SUV, initially a 1-cm spheric volume of interest (VOI) was placed over 5 bone sites: T12, L5, sacrum, right iliac bone, and right femur. For each patient, the mean SUV(max) for all sites was generated. Afterward, a threshold value of normal bone uptake was established. Subsequently, skeletal tumor burden was determined by generating volumetric data using a whole-body segmentation method. Any SUV(max) below the normal threshold was excluded from analysis, as were VOIs not related to metastatic disease. Statistics for the remaining VOIs were then generated and defined as the skeletal metastatic tumor burden by 2 parameters: total lesion fluoride uptake above an SUV(max) of 10 (TLF(10)) and fluoride tumor volume above an SUV(max) of 10 (FTV(10)). TLF(10) and FTV(10) reproducibility was determined using 2 independent and experienced PET/CT interpreters analyzing a subset of 13 (18)F-fluoride PET/CT scans. RESULTS: Mean (±SD) normal bone SUV(max) was 6.62 ± 1.55 for T12, 6.11 ± 1.73 for L5, 4.59 ± 1.74 for sacrum, 5.39 ± 1.72 for right iliac bone, and 3.90 ± 1.57 for right femur. The mean normal SUV(max) for all 543 sites was 5.32 ± 0.99. On the basis of these values, an SUV(max) threshold of 10 was chosen to exclude normal bone from the volumetric calculations. Semiautomated measurements of TLF(10) and FTV(10) exhibited high interobserver reproducibility, within ±0.77% and ±3.62% of the interinterpreter average for TLF(10) and FTV(10), respectively. CONCLUSION: Determination of skeletal tumor burden with (18)F-fluoride PET/CT is feasible and highly reproducible. Using an SUV(max) threshold of 10 excludes nearly all normal bone activity from volumetric calculations.